2015
DOI: 10.1017/s0952523815000103
|View full text |Cite
|
Sign up to set email alerts
|

The medial parietal occipital areas in the macaque monkey

Abstract: The number, location, extent, and functional properties of the cortical areas that occupy the medial parieto-occipital cortex (mPOC) have been, and still is, a matter of scientific debate. The mPOC is a convoluted region of the brain that presents a high level of individual variability, and the fact that many areas of mPOC are located within very deep sulci further limits the possibility to investigate their anatomo-functional properties. In the present review, we summarize the location and extent of mPOC area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 54 publications
7
29
0
Order By: Relevance
“…This region has been traditionally assigned to PO/V6, usually being combined with a lower quadrant representation in the parietooccipital sulcus to form a complete representation of peripheral vision (Fig. 1; Colby et al, 1988; Neuenschwander et al, 1994; Gamberini et al, 2015). However, as illustrated in Figures 4 and 7, this lower quadrant representation can be seen as a straightforward continuation of V3d.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This region has been traditionally assigned to PO/V6, usually being combined with a lower quadrant representation in the parietooccipital sulcus to form a complete representation of peripheral vision (Fig. 1; Colby et al, 1988; Neuenschwander et al, 1994; Gamberini et al, 2015). However, as illustrated in Figures 4 and 7, this lower quadrant representation can be seen as a straightforward continuation of V3d.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in order to avoid multiplication of names, we favor retaining the designation V6, with the provision that this area is not separated from V2 by a strip of V3d, as proposed previously (e.g. Gamberini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the first evidence for spatiotopic coding came from single-cell recoding in the monkey, showing that neurons in V6 have spatial tuning invariant with gaze position (Galletti et al 1993), later also reported in the ventral intraparietal cortex (VIP) by Duhamel et al (1997). Subsequently, the same group showed that V6 is organized in a retinotopic fashion, with individual cells showing a sensitivity to the real motion of objects in allocentric coordinates (Gamberini et al 2015). Even in the primary visual cortex, V1, the selectivity has been shown to modulate to some extent with gaze (Celebrini et al 2009;Durand et al 2010).…”
mentioning
confidence: 92%
“…1). Although proposals regarding the boundaries of PO/V6 continue to evolve (Gamberini et al, 2015), it is generally agreed that receptive fields of neurons in this region emphasize peripheral vision. Moreover, models proposed by various groups converge on the idea that PO/V6 encompasses a representation of the lower quadrant in the parietooccipital sulcus, as well as a representation of the upper visual field on the mesial surface of the hemisphere.…”
Section: Introductionmentioning
confidence: 99%